Community-Based Approach in A Small Scale Irrigation Project in Indonesia: Ways and Advantages - Bambang Istijono; Taufika Ophiyandri (Institute of Research and Community Outreach - Petra Christian University, 2015)
The implementation of community-based approach, where community can control a government owned infrastructure project, is rarely found. However, Sumatra River Basin Organization (BWSS) V successfully implemented a small scale irrigation project using this method in West Sumatra Province, Indonesia. This paper aims to describe how this policy was implemented, highlight its milestones, and discuss the advantages of its application. A detailed literature review and semi structured interviews were conducted to achieve the objectives. It was found that the implementation of community-based approach can bring about a sense of belonging, sustainability, and a source of income for the community. Hence, the project was finished on time within budget with high quality materials. In some cases the quantity of the project was more than it was targeted. The key policy that contributed to the success was trusting community to control the project and making sure that the proposed project came from the community.